2009
DOI: 10.1590/s0073-47212009000400009
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento de Aegla itacolomiensis (Crustacea, Decapoda) em um arroio da Mata Atlântica no sul do Brasil

Abstract: . The specimens were collected by dip net, sexed and after the cephalotorax measured, the animals were brought back to the stream. The growth estimated by cephalotorax length for males and females of A.itacolomiensis was analized by absolut distributional size-classes frequency. The modal frequency of cephalotorax lenght was calculated. The growth was estimated trought the modal progression. The growth curves in cefalotorax length for males and females are described respectively by the equations: C t = 23.21 [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
3
4
0
3
Order By: Relevance
“…Conversely, the time at which the size at onset of morphometric maturity is attained may vary among species. In accordance to the somatic growth pattern data compiled by Silva-Gonçalves et al (2009), Cohen et al (2011 and Trevisan and Santos (2011), complemented by results obtained by Chiquetto-Machado et al (2016), species found in lower latitude locations (<25º) tend to grow more slowly and, thus, are expected to take longer to attain morphometric maturity than those found in higher latitude regions.…”
Section: Nauplius 24: E2016010supporting
confidence: 72%
“…Conversely, the time at which the size at onset of morphometric maturity is attained may vary among species. In accordance to the somatic growth pattern data compiled by Silva-Gonçalves et al (2009), Cohen et al (2011 and Trevisan and Santos (2011), complemented by results obtained by Chiquetto-Machado et al (2016), species found in lower latitude locations (<25º) tend to grow more slowly and, thus, are expected to take longer to attain morphometric maturity than those found in higher latitude regions.…”
Section: Nauplius 24: E2016010supporting
confidence: 72%
“…This occurrence of sexual dimorphism in structures which play important roles in sexual interaction might be a strong indication that sexual selection operates on the determination of body size difference between males and females of a population (Shine, 1989;Cohen et al, 2011). Mortality, migration, responses to environmental conditions (Gonçalves et al, 2006), and resource use (Silva-Gonçalves et al, 2009) have also been suggested.…”
Section: Discussionmentioning
confidence: 98%
“…As curvas de crescimento de machos e fêmeas apresentaram-se diferentes. Assim como em A. platensis , A. longirostri (Silva-Castiglioni et al, 2006) A. jarai Bond-Buckup & Buckup , 1994(Boss Jr. et al, 2006 e A. itacolomiensis Bond-Buckup & Buckup , 1994(Silva-Gonçalves et al, 2009, a taxa de crescimento (k) é maior nos machos, enquanto A. leptodactyla (Noro & Buckup, 2003) (Hartnoll 1982(Hartnoll , 1985. Diferentes taxas de mortalidade entre os sexos (Wolf et al, 1975), migração (Montague, 1980), maior facilidade de um dos sexos suportar as adversidades ambientais, desequilíbrio espacial e temporal na utilização dos recursos e padrões comportamentais diferenciados entre os sexos (Giesel, 1972) podem ser alguns dos fatores que, também, influenciam na diferença de tamanho entre machos e fêmeas de uma determinada espécie.…”
Section: Methodsunclassified
“…itacolomiensis Bond-Buckup & Buckup , 1994(Silva-Gonçalves et al, 2009. Para essas espécies citadas, a taxa de crescimento (k) é maior nos machos que nas fêmeas, enquanto A. leptodactyla (Noro & Buckup, 2003) não apresenta diferença significativa no k entre os sexos.…”
Section: Introdução Geralunclassified
See 1 more Smart Citation